2021
DOI: 10.1038/s41598-021-90327-y
|View full text |Cite
|
Sign up to set email alerts
|

Human granulocytic anaplasmosis in a Single University Hospital in the Republic of Korea

Abstract: To date, only a few studies have analyzed the clinical characteristics and genetic features of human granulocytic anaplasmosis (HGA) in South Korea. Thus, in this study, we investigated the clinical characteristics of HGA and methods used for clinical diagnosis. The clinical characteristics of patients with HGA were studied retrospectively. We reviewed the medical charts of 21 confirmed patients with HGA admitted to the Chosun University Hospital, located in Gwangju, South Korea. Twenty-one HGA patients visite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The data on 221 patients who received a diagnosis of SFTS at 21 hospitals in Korea and 33 patients who received a diagnosis of HGA at the Chosun University Hospital from 2013 to 2020 were analyzed and compared 17 , 20 .…”
Section: Methodsmentioning
confidence: 99%
“…The data on 221 patients who received a diagnosis of SFTS at 21 hospitals in Korea and 33 patients who received a diagnosis of HGA at the Chosun University Hospital from 2013 to 2020 were analyzed and compared 17 , 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Gel electrophoresis results have shown that the 16S rRNA gene exists in 24 samples. This identification enables confirmation of the organism as A. platys according to Bakken (19). Phylogenetic tree analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Normal and nested PCR were used in this study for diagnosis of A. platys. Two sets of primers (EE-1, EE-2, EE-3, and EE-4) were used to detect and amplify the targeting partial region of 16S rRNA (19). Interestingly, these primers were used in previous work to detect A. Phagocytophiulm before the deposition of the A. platys sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have discussed all the possible land ll metals [26][27][28][29][30][31] and its environmental as well as health effects. Therefore, the review can give information regarding the hazardous metals which can present in land ll and came in the natural stream and creates health hazardous effect to the living being.…”
Section: Discussionmentioning
confidence: 99%